HIF-1α Regulated WTAP Overexpression Promoting the Warburg Effect of Ovarian Cancer by m6A-Dependent Manner. (12th June 2022) - Lyu, Yuanyuan; Zhang, Yilin; Wang, Yuhan; Luo, Yonghong; Ding, Huafeng; Li, Peiling; Ni, Guantai
Abstract : N6-methyladenosine (m6A) RNA methylation has been determined to execute crucial functions in tumorigenesis and cancer development. WT1-associated protein (WTAP) has an important "writer" role in m6A modification, and it is also a nuclear protein that colocalizes with splicing factors and plays a critical role in cell function and cancer progression. However, little is known about the role of WTAP in ovarian cancer (OC) and its mechanisms. In this study, we found for the first time that hypoxia-inducible factor (HIF)-1 α could positively regulate increased expression of WTAP under hypoxia. And further results revealed that WTAP expression was closely associated with the clinicopathological features of OC, and high expression of WTAP predicted low survival rate in patients with OC. In addition, cell proliferation and invasive capacity were significantly reduced after knockdown of WTAP expression in OC cells. However, cell proliferation and invasive ability were significantly enhanced after overexpression of WTAP. Additionally, we find that WTAP interacts with DGCR8 (a crucial chip protein) to regulate the expression of microRNA-200 (miR-200) in an m6A-dependent way. Further experiments showed that the key glycolysis enzyme HK2 could be positively regulated by miR-200, which significantly affected the intracellular Warburg effect. In conclusion, this is considered uncovered that upregulation of WTAP expression by HIF-1 α intercedes with miRNA processing, accelerates the Warburg impact, and advances the event and advancement of tumor, thus giving a novel viewpoint on m6A adjustment in OC movement.